2021
DOI: 10.51574/jrip.v1i2.42
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation CLT Approach to Improve Students Speaking Skills

Abstract: The goal of this study is to find out how instructors employ the Communicative Language Teaching approach in the English classroom, as well as the strategies and resources they use to help students develop their speaking skills.This can be seen from the class activities, speaking materials until the strategies that has been implemented in some research. This article takes the form of a review of documents and literatures, with an evaluation of knowledge as the basis. As a result, as a teacher, you may learn fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In addition, in hospitality classes, CLT strategies such as active discussions and group work significantly improve students' speaking skills (Rafidah Binti Rostan et al, 2023). A review of the application of CLT in various countries highlights its role in improving speaking skills, although challenges such as lack of authentic materials and large class sizes still exist (Wahyuni et al, 2021). Furthermore, a study in Sudan revealed that teachers find CLT beneficial for sharing knowledge and improving students' speaking skills, despite facing obstacles such as inadequate resources (Abdelmageed &;Omer, 2020).…”
Section: Differences Between Communicative Approach and Conventional ...mentioning
confidence: 99%
“…In addition, in hospitality classes, CLT strategies such as active discussions and group work significantly improve students' speaking skills (Rafidah Binti Rostan et al, 2023). A review of the application of CLT in various countries highlights its role in improving speaking skills, although challenges such as lack of authentic materials and large class sizes still exist (Wahyuni et al, 2021). Furthermore, a study in Sudan revealed that teachers find CLT beneficial for sharing knowledge and improving students' speaking skills, despite facing obstacles such as inadequate resources (Abdelmageed &;Omer, 2020).…”
Section: Differences Between Communicative Approach and Conventional ...mentioning
confidence: 99%
“…Speaking skills involve the proficient use of language-building elements such as grammatical structure, vocabulary, intonation, and pronunciation. Students often have difficulty in social communication that as not being able to express their views or thoughts, or they understand what others say but cannot report it (Wahyuni et al, 2021). This can be due to many influencing factors such as lack of regular speaking practice environment, motivation to learn, and confidence of learners.…”
Section: Definition Of Speaking Skillmentioning
confidence: 99%
“…Many researchers found that Communicating Language Teaching approach should be used in teaching Foreign Language (FLT) through interactive activities in the classroom. Wahyuni (2021) pointed out that students actively join in-class activities that are more visual and realistic with CLT. Toro et al (2018) stated that the CLT approach involves learning through interaction and communication rather than learning through learners' memorization.…”
Section: Introductionmentioning
confidence: 99%